Optimization of Flat Product Production Costs by Implementing a Robotic Station: Experimental Approach - Niekurzak, Mariusz (Management and Production Engineering Review, 2026)
The aim of this study was to analyse the impact of technological modifications in the production cycle of flat components on reducing production costs. The research involved a detailed analysis of production processes, identification of key areas requiring improvement, and the development of new technological solutions. As part of the study, changes were implemented in the production process, and their effect on production costs was thoroughly evaluated. The technological modification in the manufacturing of the “metal support bracket” was designed to enhance efficiency by reducing unit production time and assessing the effect of this change on overall production performance. The main innovations included the introduction of a machining centre that integrated drilling, chamfering, and threading operations into a single process. This significantly reduced both unit production time and cost while eliminating machine downtime. Additionally, powder coating was replaced with electroplating, which resolved issues related to hole narrowing and ensured the maintenance of precise technical dimensions. The implemented changes resulted in a shorter production cycle, improved product accuracy and quality, and reduced machine downtime. The analysis demonstrated that these modifications positively influenced the enterprise’s competitiveness, generating substantial cost savings. This work provides a practical example of the application of industrial innovation, contributing to cost reduction, shorter production cycle times, and enhanced precision and quality of products.